Tuberculous meningitis of severe expression in pediatrics - Reyes Florián, Guiliana (2020)
Tuberculosis (TB) remains a major public health problem worldwide. The actual magnitude of this epidemic is underestimated due to difficulties in diagnosis in children and the limited reporting of this disease. Diagnosis of childhood TB represents a challenge, since the infection in the child usually presents with nonspecific clinical manifestations and is often asymptomatic, which delays the diagnosis, leading to this age group at a high risk of disseminated infection. We describe the case of a preschool boy with meningeal tuberculosis, with a subacute clinical presentation of fever, progressive sensory disorder, and signs of endocranial hypertension. The epidemiological background allowed guiding the diagnosis and the start of antituberculous therapy. The patient's clinical evolution was torpid, he developed very serious complications, with a fatal outcome.